Politicizing Europe: The Challenge of Executive Discretion - Jonathan White (London School of Economics and Political Science (LSE), European Institute, 2014)
Political decision-making in the Euro-crisis has relied heavily on executive discretion, exercised at speed and rationalised with reference to the pressing demands of emergency. This paper explores the challenges raised for political opposition, notably challenges of a temporal kind. With its deviations from policy and procedural norms, discretionary politics tends towards a politics without rhythm, leading to major asymmetries between decision-makers and voices of opposition. These centre on issues of timing and the ability to identify authorship and content of decisions. Such asymmetries arguably correspond to an underlying one between the temporality of political decision-making and of contemporary finance capitalism, with agents of the former increasingly inclined to pursue 'fast policy' as a means to keep pace. A democratic response is likely to involve strengthening and synchronising the rhythms of parliamentary politics, as well as being receptive to forms of opposition less reliant on the rhythms that discretion subverts.
Keywords: 330; politicization; democracy; time; executive power; European Union